2015
DOI: 10.1104/pp.15.00009
|View full text |Cite
|
Sign up to set email alerts
|

S-Sulfhydration: A Cysteine Posttranslational Modification in Plant Systems

Abstract: Hydrogen sulfide is a highly reactive molecule that is currently accepted as a signaling compound. This molecule is as important as carbon monoxide in mammals and hydrogen peroxide in plants, as well as nitric oxide in both eukaryotic systems. Although many studies have been conducted on the physiological effects of hydrogen sulfide, the underlying mechanisms are poorly understood. One of the proposed mechanisms involves the posttranslational modification of protein cysteine residues, a process called S-sulfhy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
250
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 270 publications
(255 citation statements)
references
References 62 publications
5
250
0
Order By: Relevance
“…These observations are also supported by in vitro biochemical assays in Arabidopsis using H 2 S donors. Thus, it has been shown that H 2 S positively regulates ascorbate peroxidase activity (Aroca et al ) but exerts an inhibitory effect on catalase activity (Corpas et al ). A recent proteomic study of A. thaliana leaves reported that both NADP‐ICDH and NADP‐ME are targets of persulfidation (Aroca et al ) [which is a posttranslational protein modification, similar to protein S ‐nitrosation (Cys‐SNO), mediated by H 2 S that affects thiol groups (Cys‐SSH)].…”
Section: Discussionmentioning
confidence: 99%
“…These observations are also supported by in vitro biochemical assays in Arabidopsis using H 2 S donors. Thus, it has been shown that H 2 S positively regulates ascorbate peroxidase activity (Aroca et al ) but exerts an inhibitory effect on catalase activity (Corpas et al ). A recent proteomic study of A. thaliana leaves reported that both NADP‐ICDH and NADP‐ME are targets of persulfidation (Aroca et al ) [which is a posttranslational protein modification, similar to protein S ‐nitrosation (Cys‐SNO), mediated by H 2 S that affects thiol groups (Cys‐SSH)].…”
Section: Discussionmentioning
confidence: 99%
“…Plant proteins also undergo this posttranslational modification [76]. Cysteine metabolizing enzymes have been identified in plants, which catalyze the production of H 2 S from L-cysteine [77, 78, 79].…”
Section: Physiologic Roles Of Sulfhydrationmentioning
confidence: 99%
“…More recently, many research groups found that a number of abiotic stresses also can trigger H 2 S signaling, while exogenously applied H 2 S can induce cross-adaptation to multiple stresses, indicating that H 2 S represents a potential candidate signal molecule in cross-adaptation in plants (Li, 2013; Lisjak et al, 2013; Calderwood and Kopriva, 2014; Hancock and Whiteman, 2014; Fotopoulos et al, 2015; Guo et al, 2016). However, H 2 S acts as a signal molecule in plants cross-adaptation, the following questions need to be further answered: (1) Receptor or target of H 2 S. Due to H 2 S is easy to penetrate the cell membrane, maybe there is no H 2 S receptor in plant cells, but Li et al (2011) and Aroca et al (2015) found that H 2 S could modify the activity of some proteins with sulfhydryl (-SH) by sulfhydrylation (-SSH), whether these proteins are the receptors of H 2 S needs to be further research. (2) Physiological concentration of H 2 S. Many assay methods for H 2 S including colorimetric, fluorescence-based, gas chromatographic and electrochemical methods give highly contrasting results ( Table 2 ; Peng et al, 2012; Li, 2015b), so accurate physiological concentration of H 2 S in plant cells or organelles is waiting for uncovering.…”
Section: Conclusion and Future Prospectivementioning
confidence: 99%